2009
DOI: 10.1111/j.1526-4610.2009.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Momentary Relationship Between Stress and Headaches in Adolescent Girls

Abstract: Perceived stress and head pain was highly correlated in these female adolescents. Given the large population of teens affected by headaches, a plausible next step would be to validate these results in other samples and to determine methods with which to identify teens who may be at risk for a pattern of increasing stress and headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Reported significant correlates of compliance among studies with nonclinical participants included gender [39-41], ethnicity [36,40], health condition [42], and baseline affect [41,43]. Weekday status [36,44] and participant age [36,40] were reportedly not associated with prompt completion rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported significant correlates of compliance among studies with nonclinical participants included gender [39-41], ethnicity [36,40], health condition [42], and baseline affect [41,43]. Weekday status [36,44] and participant age [36,40] were reportedly not associated with prompt completion rate.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that 5 studies documented reasons for missed assessments. These reasons included participants’ engagement in competing activities [42,47], device malfunction [36,46,47], not hearing the notification [42], and participant forgetfulness [30,46]. …”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies focused on stressors by asking open-ended questions about life events and situations that are generally considered to be related to stress. Other recent studies evaluated perceived stress by asking for the frequency of 'feeling stressed' or by implementing visual analogue scales that should represent the current level of stress, but without differentiation between the origin of the stressors (10)(11)(12). In contrast, the Trier Inventory of Chronic Stress (TICS) is an instrument which allows the assessment of the individual's appraisal of potentially stressful situations (18).…”
Section: Introductionmentioning
confidence: 99%
“…Still, they were more likely to show reduced anxiety levels when in the company of friends. Other studies have used electronic diaries among adolescents with depression29 and have studied the relationship between stress and headaches 30. Using the internet as a data collection tool has also been acceptable for participants: it offers real-time information28,31 and it is easy to use 32…”
Section: Introductionmentioning
confidence: 99%